Influence of the beginning of soil preparation and the number of rows for sowing relationship on the establishment of multiple mixtures of creeping legumes associated with grasses - Ruiz, Tomás E.; Febles, Gustavo; Díaz, H.; Díaz, J. (Cuban Journal of Agricultural Science, 2016)
An experiment was conducted for studying the effect of the starting time of soil preparation and the number of the rows for sowing on the establishment of multiple mixtures of creeping legumes associated with grasses. A random block design, in factorial arrangement with four replications was applied. Factors were: time of starting soil preparation (February, March and April) and the number (2:2 and 2:3) of rows for sowing (grass-legume) and an unsown control. Trials were repeated in time. Legumes were Centrosema pubescens (centro), Macroptilium atropurpureum (siratro), Neonotonia wightii (glycine), Stylosanthes guyanensis (stylo) and Calopogonium mucunoides (Calopogonium), associated with Panicum maximum (guinea grass). They were sown in a red ferrallitic soil at the beginning of the rainy season. The time of starting soil preparation for the sowing in February showed important values for legume yield (2.2 t DM/ha) and grasses (4.3 t DM/ha). The highest weed incidence in all treatments at the end of the rainy period was present in the areas where the association was not sown (1.06 – 2.68 t DM/ha). This incidence was lower as the time of preparation was shorter. The best performance for the rows for sowing (grass-legume) was present for the 2:3 relationship, in measurements as important as higher number of legumes/m2 and lower number of weeds/m2. As the presence of weed plants increased, the amount of rooted points was affected. The number of legume plants/m2 showed differences and was reflected on their yield. It was lower for March and April treatments. It is concluded that starting soil preparation in February favors the harmonic plant development, the rooted points of creeping legumes, as well as the balance of the system components and their persistency.Key words: soil preparation, row relationship, creeping legumes, grasses, weeds